2016
DOI: 10.1111/bju.13623
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic potential to regional lymph nodes with Gleason score ≤7, including tertiary pattern 5, at radical prostatectomy

Abstract: This study supports our previous finding that men with GS 6 (GG1) at RP have no risk of LN metastases. These findings also support the 2014 revisions to the Gleason grading system where 3 + 3 with T4 (2005 modified grading system) is now considered 3 + 4 (GG2), with a comment on percent pattern 4, because <5% pattern 4 increases the risk of LN metastases. It also supports keeping 3 + 4 (GG2) with T5 (<5% pattern 5) and 4 + 3 (GG3) with T5 with their respective grade groups, with a notation of T5 because the <5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…This is also supported by the low rate of lymph node metastases in men with GG2 Pca. Diolombi and Epstein [22] found 0.6% pelvic lymph node metastasis among 3235 men with GG2 Pca at RP without stratification for CR/IDC. In another GG2 RP cohort, lymph node metastasis were present in 12/228 (5.3%) patients with CR/IDC but in none of 192 men without CR/IDC [23].…”
Section: Discussionmentioning
confidence: 98%
“…This is also supported by the low rate of lymph node metastases in men with GG2 Pca. Diolombi and Epstein [22] found 0.6% pelvic lymph node metastasis among 3235 men with GG2 Pca at RP without stratification for CR/IDC. In another GG2 RP cohort, lymph node metastasis were present in 12/228 (5.3%) patients with CR/IDC but in none of 192 men without CR/IDC [23].…”
Section: Discussionmentioning
confidence: 98%
“…While the ISUP 2014 report suggested that a TP be defined exclusively as truly minor/limited (,5%) and should not alter the Grade Group, there is conflicting evidence in contemporary cohorts. [9][10][11][12]15,16,18 Importantly, although reporting of TPs is recommended for RP specimens, there is discordance with clinical predictive models that do not include TP in a standard fashion. [23][24][25] This is likely due to the reality that almost all TP studies are single institution reports, may be underpowered to show clear prognostic significance in multivariable analysis, often have short follow-up, and have not yet shown utility in clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] While most of so-called tertiary grading reported in the literature refers to a higher grade-typically pattern 5-the term has been used variably regarding extent, ranging from a more limited, minor, or less than 5% highergrade carcinoma component in initial publications 3,4 to a third most common pattern of any percentage. [6][7][8][9][10][11][12][13][14][15][16][17][18] The accepted method for reporting ''tertiary'' patterns also differs between needle biopsy and radical prostatectomy (RP). As codified by the International Society of Urologic Pathology (ISUP) 2005 and 2014 grading conferences, cases with 3 patterns on needle biopsy should be graded by using a ''first plus worst'' (most common þ next highest grade) strategy.…”
mentioning
confidence: 99%
See 2 more Smart Citations